Unemployment Problem among Youths of Uttarakhand State(A Case Study Conducted in 2009 of New Tehri District) - Rani, Preeti; Agarwal, M. K (Journal of Commerce and Trade, 2011)
Unemployment is the basic problem which has given birth to a number of connected problems, such as poverty, social disorder, insecurity, maintenance of law and order etc in the State of Uttarakhand. At the time of establishment of Uttarakhand State though the government en made and announced many policies to recover the problem of unemployment, yet it is also the big truth that the government remained failure to achieve the target of full employment. Various factors are responsible for this phenomenon which includes a large number of old age people, lack of employment among women, lack in mobility, cold weather, natural problems, illiteracy, geographical conditions etc. Moreover, also largely dependence on government organizations, lack of industries, ignorance about small and cottage industries are the big hurdles in the employment generation in this State. This problem can be removed by raising the level of investment in hill areas’ small villages and towns in Uttarakhand. Accelerating the process of industrialization can also help to reduce the level of unemployment. Government policies and planning should be employment-oriented so that it may prove meaningful for the masses. Also a long-term population policy along with an effective employment policy can rid of Uttarakhand State from the menace of unemployment in the years to come.